MORPHOLOGICAL AND FUNCTIONAL FEATURES OF THE NERVOUS SYSTEM DEVELOPMENT IN ONTOGENESIS - Литвиненко, Н.В.; Пурденко, Т.Й.; Гладка, В.М.; Силенко, Г.Я. (World of Medicine and Biology, 2016)
The chain of successive biochemical, physiological and morphological changes, which are specific to each of the periods of individual development of the body, underlies the ontogenesis. The basic principle in the maturation of the brain is manifested by the fact that onto- and phylogenetically older structures mature earlier. For the development of each of the next levels, the complete maturation of the previous one is essential; besides, the overlying structures are not simply “built on” over the existing ones, but actually influence their further development. The complex hierarchical structure of the nervous system is formed, in which the basic regulatory role in the development process is entrusted to the cortex of the cerebral hemispheres.